Variable rate liquidity tenders - Tuomas Välimäki (Bank of Finland, 2002)
This paper constructs an equilibrium model for the short-term money market, when the central bank provides liquidity via variable rate tenders.The relation between market rate of interest and liquidity is derived from a single bank's profit maximisation problem in the interbank market, and the CB determines its liquidity provision by minimising a quadratic loss function that contains both deviations of expected market rate from CB target rate and differences between liquidity supply and target liquidity.We model equilibrium bid behaviour in the tenders and explain the underbidding phenomenon resulting from the minimum bid rate.We also show that, when maturities of consecutive operations overlap, the expected market interest rate will rise above the CB's target whenever a target rate change (hike or cut) is expected to occur in the same reserve maintenance period.Finally, we review the data from the ECB variable rate tenders and find that the ECB has been fairly liquidity oriented in its allotment decisions.
URN:NBN:fi:bof-20140807665
Keywords: 330; money market tenders; liquidity policy; bidding; central bank operational framework